Premature ovarian insufficiency – hormone replacement therapy and management of long-term consequences - Machura, Paulina; Grymowicz, Monika; Rudnicka, Ewa; Pięta, Wojciech; Calik-Ksepka, Anna; Skórska, Jolanta; Smolarczyk, Roman (Menopause Review/Przegląd Menopauzalny, 2018)
Premature ovarian insufficiency (POI) correlates with increased risk of cardiovascular diseases, osteoporosis, genitourinary syndrome, and other symptoms of prolonged oestrogen deprivation. Properly selected therapy improves the quality of women’s lives and reduces the risk of mortality. There is a wide spectrum of available oestrogen and progestogen formulations restoring proper levels of serum sex steroid hormones. The treatment should be implemented at recognition of the POI and continued to at least the age of natural menopause. Transdermal oestradiol and oral or vaginal progesterone administration provide the most physiological sex steroid replacement therapy. Patients’ views and individual preference according the route, dose, and regimen of hormonal treatment have to be taken into consideration in order to achieve high compliance rates. Women with POI should be managed by a multidisciplinary team, such as a gynaecologist, endocrinologist, dietitian, and psychologist.